Reliability Testing and Validation of the Drug Attitude Scale - Campbell, Stephen N.; Chang, Annie (Substance use & misuse, 2006)
This study was designed to provide reliability testing and validity information of the Drug Attitude Scale (DAS). One hundred twenty-eight subjects were drawn from a residential substance abuse1 treatment program within a community mental health center. Seventy-five percent of the subjects were males and 25% were females. Age ranged from 18 to 58 years. For the entire sample, coefficient alpha was found to be 0.87. Reliability estimates for the two subscales were also found to be quite similar. Clinical construct validity utilizing factor analysis strongly support the two-dimensional nature of the DAS and the accuracy of the instrument's scoring key. Initial testing of the DAS suggests that the scale represent a useful addition to the area of substance user assessment and rehabilitation.